f(

g(0, 1,

a -> b

a -> c

R

↳Dependency Pair Analysis

F(x,y,z) -> G(x,y,z)

G(0, 1,x) -> F(x,x,x)

Furthermore,

R

↳DPs

→DP Problem 1

↳Instantiation Transformation

**G(0, 1, x) -> F(x, x, x)**

f(x,y,z) -> g(x,y,z)

g(0, 1,x) -> f(x,x,x)

a -> b

a -> c

innermost

On this DP problem, an Instantiation SCC transformation can be performed.

As a result of transforming the rule

one new Dependency Pair is created:

F(x,y,z) -> G(x,y,z)

F(z',z',z') -> G(z',z',z')

The transformation is resulting in no new DP problems.

Duration:

0:00 minutes